Dialogues LAGEBES: Contributions to capixaba education in the context of covid-19 - Lopes de Almeida, Thaciana; Campos de Oliveira, Thalia; Ferrari, Lorrainy; Cardoso de Araujo, Gilda (Guará Journal, 2022)
This article aims to analyze the contributions of the Diálogos Lagebes outreach initiative to education, using Thiollent's (2005) action research as a methodological framework. Faced with the uncertainties of the COVID-19 pandemic, the Espírito Santo Basic Education Management Laboratory (Lagebes) held seven live YouTube sessions to engage with teachers, parents, students, administrators, and the general public about the implications of returning to in-person classes, safety measures, and working conditions. The concluding remarks indicate that the Diálogos Lagebes initiative expanded its social role as an outreach initiative, strengthening the university's three pillars of research, teaching, and outreach. Furthermore, it promoted a comprehensive and critical dialogue on the infrastructure conditions of public schools in the state of Espírito Santo.
Keywords: Extension; Education; Pandemic